Study of gas-liquid mixing in stirred vessel using electrical resistance tomography - Sher, Farooq; Sajid, Zaman; Tokay, Begum; Martin, Khzouzc; Sadiqd, Hamad (Wiley, 2016)
This study presents a full operation and optimisation of a mixing unit; an innovative approach is developed to address the behaviour of gas-liquid mixing by using Electrical Resistance Tomography (ERT). The validity of the method is investigated by developing the tomographic images using different numbers of baffles in a mixing unit. This technique provided clear visual evidence of better mixing that took place inside the gasliquid system and the effect of a different number of baffles on mixing characteristics. For optimum gas flow rate (m3/s) and power input (kW), the oxygen absorption rate in water was measured. Dynamic gassingout method was applied for five different gas flow rates and four different power inputs to find out mass transfer coefficient (KLa). The rest of the experiments with one up to four baffles were carried out at these optimum values of power input (2.0 kW) and gas flow rate (8.5×10-4 m3/s). The experimental results and tomography visualisations showed that the gasliquid mixing with standard baffling provided near the optimal process performance and good mechanical stability, as higher mass transfer rates were obtained using a greater number of baffles. The addition of single baffle had a striking effect on mixing efficiency and additions of further baffles significantly decrease mixing time. The energy required for complete mixing was remarkably reduced in the case of four baffles as compared to without any baffle. The process economics study showed that the increased cost of baffles installation accounts for less cost of energy input for agitation. The process economics have also revealed that the optimum numbers of baffles are four in the present mixing unit and the use of an optimum number of baffles reduced the energy input cost by 54%.